2002
DOI: 10.1159/000058003
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Propionate Downregulates Nasal Fibroblast Functions Involved in Airway Inflammation and Remodeling

Abstract: Background: Besides being highly effective in the treatment of allergic and nonallergic rhinitis with eosinophilia, intranasal corticosteroids appear to be useful in reducing nasal polypoid lesions and the likelihood of polyp recurrence after surgery. We evaluated the ability of fluticasone propionate to downregulate fibroblast functions related to nasal inflammation and remodeling. Methods: Primary nasal polyp tissue-derived fibroblasts were stimulated with tumor necrosis factor (TNF)-α or interleukin (IL)-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 33 publications
5
35
0
1
Order By: Relevance
“…These data are consistent with the current authors' previous findings, where a 91% increase in DNA synthesis above untreated fibroblasts isolated from subjects with mild asthma was demonstrated [7]. However, in a different model system by SILVESTRI et al [10], fluticasone at concentrations ranging from 0.1-100 nM was found to decrease proliferation and eotaxin expression from fibroblasts cultured from nasal polyps. In addition to the differences in the model system, fluticasone is also 10-100 times more potent than dexamethasone, which may explain the disparate results between these studies [28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data are consistent with the current authors' previous findings, where a 91% increase in DNA synthesis above untreated fibroblasts isolated from subjects with mild asthma was demonstrated [7]. However, in a different model system by SILVESTRI et al [10], fluticasone at concentrations ranging from 0.1-100 nM was found to decrease proliferation and eotaxin expression from fibroblasts cultured from nasal polyps. In addition to the differences in the model system, fluticasone is also 10-100 times more potent than dexamethasone, which may explain the disparate results between these studies [28].…”
Section: Discussionsupporting
confidence: 92%
“…Dexamethasone increased DNA synthesis in cultured airway fibroblasts from asthmatics, an effect that was most prominent in cells from mild asthmatics. Whether this response is beneficial or detrimental is not clear; however, it does stand in contrast to the effects of corticosteroids on fibroblasts in other organ systems, where proliferation was either decreased or unchanged [8][9][10]. To further investigate the effects of corticosteroids on airway fibroblast function in asthma, the present authors also examined the effect of dexamethasone on cell cycle proteins and cell cycle progression in airway fibroblasts cultured from asthmatic individuals.…”
mentioning
confidence: 99%
“…This effect on NF-κB in nasal polyp fibroblasts had already been suggested by Silvestri et al 7 and by our group 21 , although this is the first in vitro study to confirm the effect of FP on NF-κB translocation for nasal polyps.…”
Section: Discussionsupporting
confidence: 82%
“…Varela et al reported a similar finding in cultivating fibroblasts from nasal polyps, which, upon exposure to this steroid, inhibit the synthesis of cellular adhesion molecules [33]. In a similar model, Silvestri et al reported a decrease in the expression of ICAM-1, but not VCAM-1, in the presence of TNF-α [34]. Together, these mechanisms lead to an improvement in pulmonary function and a decrease in the degree of nasal polyposis [35].…”
Section: Discussionmentioning
confidence: 75%